Employee Provident Fund Organization (EPFO) : towards consumer centricity - Ravichandran, N., (SAGE Business Cases., 2018)
The Employee Provident Fund Organization (EPFO), established by the Government of India is one of the world's largest social security organisations. The purpose of EPFO is to ensure social security for industrial workers and their dependents. The EPFO's operational processes were riddled with overemphasis on rules and regulations, but were weak on transparency, accountability, effectiveness and efficiency and the 120 EPFO offices established all over the country operated in silos. Consequently, the social security and welfare of the industrial employees suffered, while all other stakeholders enjoyed a significant power to control. Recent interventions at EPFO focussed on process reengineering and ICT enablement to make EPFO more customer-centric. This case documents the transformation of EPFO from a bureaucratic, opaque organisation to a consumer centric, stakeholder friendly, transparent and accountable organisation through IT enabled operations.